2012
DOI: 10.1364/josaa.29.00a144
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical optimization of lighting spectra for naturalness, preference, and chromatic diversity

Abstract: The optimal spectral profiles of lighting for naturalness, individual preference, and chromatic diversity were estimated with psychophysical experiments in which observers selected illuminants from a set of metamers of D65 to render outdoor and indoor scenes. For naturalness, the illuminant selected was more spectrally structured than daylight and had a low color rendering index. For preference, the illuminant was similar but produced colors a little more saturated. For chromatic diversity, the spectrum was mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…There are other examples in the color domain where observers' preferences are biased towards non-naturalistic conditions. For example, in studies on preferred lighting it was shown that the illuminant preferred has a spectrum more structured than daylight and produced colors more saturated than natural illumination (Masuda & Nascimento, 2013, Nascimento & Masuda, 2012. In the luminance domain, it was shown that observers prefer images with low-skewness luminance distributions over more naturalistic high skewness distributions (Graham, Schwarz, Chatterjee & Leder, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are other examples in the color domain where observers' preferences are biased towards non-naturalistic conditions. For example, in studies on preferred lighting it was shown that the illuminant preferred has a spectrum more structured than daylight and produced colors more saturated than natural illumination (Masuda & Nascimento, 2013, Nascimento & Masuda, 2012. In the luminance domain, it was shown that observers prefer images with low-skewness luminance distributions over more naturalistic high skewness distributions (Graham, Schwarz, Chatterjee & Leder, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for scaling cone stimulation when judging lightness is somewhat analogous to the use of the MaxRGB method for illuminant estimation (Funt & Shi, 2010). Such a mechanism would also explain why white surfaces look grey when the illumination is designed to artificially enhance the perceived chromaticity of a scene (Nascimento & Masuda, 2012;Thornton, 1974): under such narrowband illumination white surfaces are not necessarily as much lighter than surfaces with very saturated colors as would normally be the case. Whatever the mechanism, our study confirms that some physical regularity of natural scenes derived by the way light is reflected by natural pigments is considered in the way we interpret the light reaching our eyes, as indeed it should be if we want to be able to rely on vision to recognize objects by their surface properties despite varying illumination.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The first four images (sizes of 820 × 820 pixels) were Scenes 1–4 from “hyperspectral images of natural scenes 2002,” which were acquired using a tunable bi-refringent filter mounted in front of the lens of a progressive-scanning monochrome digital camera [41]. The last five (sizes of 1017 × 1267 pixels) were Scenes 1–5 from “hyperspectral images of natural scenes 2004,” which were acquired using a fast-tunable liquid-crystal filter and a low-noise Peltier-cooled digital camera [42]. …”
Section: Methodsmentioning
confidence: 99%